Exploring Papuan English teachers’ strategies in enhancing junior high school students’ reading motivation - Romrome, Abel Yohanis; Sari, Rita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Reading motivation is a critical factor in English language acquisition, recognized as a significant issue for decades. Scholars have explored this topic from various perspectives, including teachers’ strategies and students’ intrinsic motivation. However, no studies have examined teachers’ strategies for fostering reading motivation among junior high school students in the Papuan context, particularly in Wamena, Papua Pegunungan Province. This study addresses this gap by investigating the strategies employed by Papuan English teachers to enhance students’ reading motivation. Data were collected using a qualitative approach through a descriptive case study. Eight Papuan English teachers participated, responding to open-ended questionnaires and semi-structured interviews. The findings indicate that teachers employed several strategies to boost reading motivation, including designing engaging reading materials, modelling enthusiasm for reading, allowing students to choose their reading texts, providing constructive feedback on reading progress, and fostering strong teacher-student relationships. These findings offer valuable pedagogical implications and practical recommendations for educators to underscore the importance of reading, thereby fostering greater student motivation to engage with texts.